An Analysis of Figurative Language in Donald Trump’s Inaugural Speech - Hamdanur, Roobby (Universitas Muhammadiyah Mataram, 2025)
This study investigated the figurative language found in Donald Trump’s Inaugural Speech on January 20th, 2025. The aim of this study was to analyze the types of figurative languages and their meanings. The method of this study was descriptive qualitative. The source of data of this study was the inaugural speech of Donald Trump. The data analyzed in this study were the words, phrases, clauses, and sentences containing figurative language. The theory used in this study was M.H. Abrams figurative language theory, and pragmatic and expressive approach to describe the meaning. The finding of this study indicated that there were 23 figurative languages found in the speech. They were personification, hyperbole, metaphor, metonymy, simile and symbolism. Personification was the most frequent figurative language. This study showed that the figurative language used in the speech was to convey ideological messages, appeal emotionally to the audience, and build persuasive narratives. This study will possibly help to enrich learning and understanding of figurative language meaning especially in political discourse.